Translation to Malayalam language and validation of Vanderbilt attention deficit hyperactivity disorder diagnostic parent rating scale: a cross-sectional study - Vijayan, Anitha; George, Babu; Bhaskaran, Deepa; Saradamma, Remadevi; M. L., Leena; Scaria, Liss Maria; M. A., Lekshmi; S., Letha (International Journal of Contemporary Pediatrics, 2026)
Background: There is a need for validated translations of tools in regional languages, to ensure uniformity in the diagnosis of attention deficit hyperactivity disorder (ADHD). The study aimed to translate Vanderbilt ADHD diagnostic parent rating scale (VADPRS) into Malayalam and validate it against INCLEN diagnostic tool for ADHD (INDT-ADHD). Methods: A cross-sectional study was conducted at a tertiary care referral center for child development and behavioral disorders, during the period of January 2022 to August 2022. Hundred and three (n=103) children in age group of 6-12 years with symptoms suggestive of ADHD were included. Parents who were unable to read Malayalam and children diagnosed with autism spectrum disorder and/or intellectual disability were excluded. Malayalam version of VADPRS was derived through forward-backward translation ensuring content, semantic, and technical validity. Validation of this translated tool was done against INDT-ADHD. As part of psychometric testing, interviews with parents and clinical examination of the children were done. Reliability and validity of the tool was analyzed by appropriate statistical methods. Results: The translated Malayalam version of VADPRS tool identified 90.3% of children had ADHD. The factor-analysis demonstrated a 2-factor structure. Discriminant validity assessed using student’s t test, showed statistically significant mean difference between two extreme groups (p=0.001). Intraclass correlation coefficient was 0.994 showing good test-retest reliability. The Cronbach’s alpha value was 0.997 indicating good internal consistency. Scale content validity index was significant with value of 0.95. The tool had a sensitivity of 98.95% (95% CI; 94.27%-99.97%) and high specificity. Negative predictive value of the tool was 90% (95% CI; 56.16%-98.44%). Conclusions: Translated version of VADPRS showed good validity against INDT-ADHD. It can be recommended for use in the Malayalam speaking population to help in diagnostic process of children with ADHD.